Wegener's Granulomatosis: Case Report - Dutta, Pradip Kumar; Jabed, Sayed Md; Huda, Md Nurul; Das, Saibal; Islam, Md Manirul; Chowdhury, Dipen; Islam, Md Shariful; Arjumand, Merina; Uddin, Rabiul Alam Md Erfan (Journal of Chittagong Medical College Teachers' Association, 2011)
DOI: 10.3329/jcmcta.v21i1.7686 Journal of Chittagong Medical College Teachers' Association 2010: 21(1):80-82